Mapping South American Latina/o Literature in the United States Interviews with Contemporary Writers - Heredia, Juanita (Literatures of the Americas, 2018)
This collection of interviews demonstrates that U.S. Latinas/os of South American background have contributed pioneering work to U.S. Latina/o literature and culture in the twenty-first century. In conversation with twelve significant authors of South American descent in the United States, Juanita Heredia reveals that, through their transnational experiences, they have developed multicultural identities throughout different regions and cities across the country. However, these authors' works also exemplify a return to their heritage in South America through memory and travel, often showing that they maintain strong cultural and literary ties across national borders. As such, they have created a new chapter in trans-American history by finding new ways of imagining South America from their formation and influences in the U.S.